Enrichment of short-chain fatty acid-producing bacteria by pH-responsive sodium alginate and chitosan-encapsulated quercetin - Bai, Qianyu; Zhao, Zhongling; Duan, Yujing; Cai, Runqiu; Chen, Yinzhu; Zhou, Chaoyu; Tian, Xinyuan; Yang, Yifei; Wu, Haiyan; Li, Mingju; You, Jia; Song, Qingyi; et al. (Frontiers in Microbiology, 2025)
IntroductionConventional approaches to treat ulcerative colitis (UC) focus on suppressing excessive inflammation and immune responses. Nevertheless, these treatments fail to address gut dysbiosis or restore the intestinal mucosal barrier effectively. Regulating the intestinal microenvironment may be pivotal to more effective therapies for UC.MethodsHerein, oral colon-targeted microspheres, sodium alginate-chitosan-encapsulate quercetin (SA-Q-CS MPs), were developed. The stability and pH responsiveness of SA-Q-CS MPs were explored. Therapeutic effects were assessed in dextran sulfate sodium (DSS)-induced ulcerative colitis in female C57BL/6 mice via 16S ribosomal RNA (rRNA) gene sequencing, Disease Activity Index (DAI) scoring, colonic histopathology, inflammatory and antioxidant levels, and intestinal barrier function.Results and DiscussionSA-Q-CS MPs markedly enhanced the overall richness and diversity of the gut microbiota, enhancing the abundance of short-chain fatty acids (SCFAs)-producing bacteria, such as Bacteroidales, Lactobacillales, and Lachnospiraceae. These changes contributed to improved intestinal barrier function, better metabolic processes, and stronger defense mechanisms, thereby ameliorating UC induced by 3% dextran sulfate sodium (DSS) in C57BL/6J mice. Compared to the DSS group, the SA-Q-CS MPs treatment group showed significant improvements, with the Disease Activity Index (DAI) and histopathological scores reduced by more than 66.9%, pro-inflammatory factor levels decreased by 65%, antioxidant levels increased over sevenfold, and tight junction protein expression elevated by more than threefold. In conclusion, this investigation presents SA-Q-CS MPs as a promising strategy for restoring gut microbiome homeostasis and providing precise treatment for UC.